Analisis Penggunaan Deiksis Dalam Film Sayap-Sayap Patah Kajian Pragmatik - Tis'ata Adhia; Ni Nyoman Yuliantari; Sabrina Sabila Dwi Hikmah; Naddia Putri Ramadani (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study departs from the assumption that film, as a representation of social reality, can serve as an object of pragmatic analysis, particularly in the study of deixis. The film Sayap-Sayap Patah, directed by Rudi Soedjarwo, was selected for its expressive utterances and because it has not been widely analyzed within linguistic studies. The objective of this research is to describe the types and forms of deixis used in the characters’ utterances. The investigation was carried out using a descriptive qualitative approach, employing observation methods and note-taking techniques. The data source consists of dialogues in the film that contain elements of personal, temporal, and spatial deixis. The data analysis technique used is the extralingual matching method, which connects language use with external contexts such as time, place, and participants. The analysis was conducted by examining each occurrence of deixis contextually within the dialogue, allowing for an in-depth understanding of its function and meaning in character interactions. The findings reveal that there are 18 deixis data found in the film, consisting of 9 personal deixis, 6 temporal deixis, and 3 spatial deixis.